Journalism that will tell about the future - López Hidalgo, Antonio (2016)
The convergence of new technologies will change the journalistic narrative in the coming years. Terms such as ‘multimedia’, ‘cross-media’, ‘transmedia’, ‘virtual’ or ‘augmented reality ‘ are just usual when it comes to new formats. We will soon have here the non-screen technology. This new reality will force the journalist to ‘think’ information and will require from them certain changes when developing the story. Access to news from the mobile device will continue to grow. In short, high-tech journalism is already here. This article discusses how some media in the US and Europe have created technological innovation laboratories to study other narratives allowed by these technologies.